Pemanfaatan Ecobrick sebagai Bahan Bangunan Alternatif dalam Program Pengabdian Masyarakat di Desa Kadumekar - Jalaludin, Jalaludin; Fatonah, Nurul Fitriani; Nurhidayat, Yayat; Salwa, Urmila (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The objective of this PKM is to utilize ecobricks as an alternative building material in the community service program in Kadumekar Village, in order to reduce the amount of plastic waste polluting the environment and provide solutions for village infrastructure development. The PKM method employs observation, socialization, mentoring, monitoring, and evaluation. The conclusion of this PKM is that the level of understanding of respondents or PKM partners before the workshop was conducted had a minimum score of 0/100 and a maximum score of 60/100, but after the workshop was conducted, the minimum score was 60/100, and the maximum score was 100/100. When averaged, the level of understanding of PKM partners changed from an average score of 28.5 (category: very poor understanding) to a drastic increase of 79 points (category: understanding). This achievement, according to the PKM team, is quite significant. The reason it did not reach 100% or 100 points is because the PKM partners wanted to quickly make ecobrick bottles without waiting for the process of inserting plastic waste into the bottles. This is one of the reasons why making ecobrick bottles takes a long time before they can be used. Additionally, this PKM has had a positive impact on the community by helping them understand the concept of Ecobrick, its usage, ensuring the quality of Ecobrick, inserting plastic waste into Ecobrick bottles, the advantages of recycled Ecobrick materials over conventional building materials, applying Ecobrick in daily activities, the benefits of ecobricks, creativity in ecobrick design, the advantages and disadvantages of ecobricks, environmental education benefits through ecobricks, and ecobrick production techniques and tools.